Instructions for a heatwave - O'Farrell, Maggie 1972- (London : Headline Publishing Group, 2013)
When a recently retired family patriarch clears out his bank account and disappears during a sweltering summer in 1976, his three children converge on their mother's home for the first time in years and track clues to an ancestral village in Ireland, where they uncover illuminating family secrets.
Keywords: Runaway husbands -- Fiction; Children of separated parents -- Fiction; London (England) -- Fiction; Domestic fiction